Kompetensi Penyuluh Agama di Kabupaten Solok Sumatera Barat - Wakidul Kohar; Muhammad Aqil; Danil Folandra (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Basically, the ultimate goal of religious education is to create a religious society. The community is expected to have an adequate understanding of religion and is shown through the practice of their religious teachings. In order for all of this to be realized, of course, extension workers must be supported with adequate competence. This study aims to describe the substantive and methodological competencies of religious instructors in Solok district, West Sumatra province. The data of this study were sourced from the results of observational interviews and literature related to the theme or research topic. The findings in this study indicate that the substantive competence of religious instructors in Solok Regency on average is still lacking in the aspect of Arabic language skills. In addition, the ability to utilize technology as a medium of da'wah is still not optimal because some extension workers are still not proficient in compressing technological media. While the methodological competence of religious instructors in Solok Regency, the majority is still conventional, not yet towards multi-dialogue da'wah. religious instructor, substantive competence, methodological competence